Interspecific association of herbaceous plant communities on different slope orientations and at different altitudes in central Yunnan grasslands - Gong, Rui; Gong, He-de (Frontiers in Plant Science, 2024)
Understanding the response of herbaceous plants to habitat changes and the mechanisms of vegetation succession is crucial to the theoretical foundation of the conservation of local vegetation. Plots were established at elevations of 1900-2200m, 2200-2500m, and 2500-2800m on both shady and sunny slopes. Four statistical methods 2×2 contingency table χ2-test, Spearman's rank correlation coefficient, AC joint coefficient, and Ochiai Index, were employed to analyze the species composition and interspecific associations within each elevation band and aspect. ImportantFindings ：(1) the number of herbaceous plant species was greater on the sunny slope than on the shady slope; the number of species was higher in the elevation bands of 1900-2200m and 2200-2500m than in 2500-2800m. (2) Both AC joint coefficient and Ochiai Index revealed that the interspecific connectivity increased as elevation